Revisiting biocrystallization: purine crystalline inclusions are widespread in eukaryotes - Pilátová, Jana; Pánek, Tomáš; Oborník, Miroslav; Čepička, Ivan; Mojzeš, Peter (The ISME journal, 2022)
Despite the widespread occurrence of intracellular crystalline inclusions in unicellular eukaryotes, scant attention has been paid to their composition, functions, and evolutionary origins. Using Raman microscopy, we examined >200 species from all major eukaryotic supergroups. We detected cellular crystalline inclusions in 77% species out of which 80% is composed of purines, such as anhydrous guanine (62%), guanine monohydrate (2%), uric acid (12%) and xanthine (4%). Our findings shifts the paradigm assuming predominance of calcite and oxalates. Purine crystals emerge in microorganisms in all habitats, e.g., in freshwater algae, endosymbionts of reef-building corals, deadly parasites, anaerobes in termite guts, or slime molds. Hence, purine biocrystallization is a general and ancestral eukaryotic process likely present in the last eukaryotic common ancestor (LECA) and here we propose two proteins omnipresent in eukaryotes that are likely in charge of their metabolism: hypoxanthine-guanine phosphoribosyl transferase and equilibrative nucleoside transporter. Purine crystalline inclusions are multifunctional structures representing high-capacity and rapid-turnover reserves of nitrogen and optically active elements, e.g., used in light sensing. Thus, we anticipate our work to be a starting point for further studies spanning from cell biology to global ecology, with potential applications in biotechnologies, bio-optics, or in human medicine.
Keywords: Purines; Biomineralization; Eukaryota; puriny; lidé; Guanine; guanin; biomineralizace; Humans